Karakteristik Torrefaksi dan Densifikasi Limbah Tandan Kosong Kelapa Sawit - Maryudi, Maryudi (Universitas Ahmad Dahlan, 2014)
Energy demand increases continuously due to the growth of industries. Most industries still rely on fossil fuel that its price commonly increases and the deposit in the universe decreases since it is not renewable resource. Indonesia is the largest palm oil producer in the world that has potential abundance biomass of empty fruit bunch (EFB) of oil palm. It can be alternative energy source. The EFB is commonly used as fuel for heat source of boiler jn the palm oil plant. Most applications were by conventional combustion process that has disadvantage of low energy value. The EFB was only chopped and grinded, and then dried prior to combustion process. This study investigates improvement of energy quality of EFB through torrefaction (or light pyrolysis) and densification process. The EFB was chopped in the small size and grinded in the form of fiber, then dried. The EFB fiber in small slices was pressed in a small steel tube and heated in the range of 200-300°C. The variables of study were duration and temperature of process. The initial heat value of EFB was 18,241 MJ/kg that slightly lower than its of kernel shell heat value 19.955 MJ/kg. The water content were found 6.28% and 4.31% for EFB and kernel shell respectively. Results have shown that torrefaction and densification have improved the calorific value of EFB in the range of 6.58-16.71% of its initial value. On the other hand, the energy yield has decreased to 97.54, 97.26 and 93.76% of its initial energy yield for torrefaction temperature of 200, 250 and 300°C respectively